2009
DOI: 10.1016/j.bbagrm.2008.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Chemical mechanisms of histone lysine and arginine modifications

Abstract: Histone lysine and arginine residues are subject to a wide array of post-translational modifications including methylation, citrullination, acetylation, ubiquitination, and sumoylation. The combinatorial action of these modifications regulates critical DNA processes including replication, repair, and transcription. In addition, enzymes that modify histone lysine and arginine residues have been correlated with a variety of human diseases including arthritis, cancer, heart disease, diabetes, and neurodegenerativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
302
0
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 328 publications
(312 citation statements)
references
References 169 publications
(250 reference statements)
3
302
0
7
Order By: Relevance
“…Previously suggested reaction mechanisms for the deacetylation process include a general acid−base catalytic pair mechanism 25,40 and a proton shuttle catalytic mechanism. 41 These mechanisms were hypothesized on the basis of previous studies of histone deacetylase-like protein (HDLP), 22,42 a homologue of HDAC found in hyperthermophilic bacteria.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Previously suggested reaction mechanisms for the deacetylation process include a general acid−base catalytic pair mechanism 25,40 and a proton shuttle catalytic mechanism. 41 These mechanisms were hypothesized on the basis of previous studies of histone deacetylase-like protein (HDLP), 22,42 a homologue of HDAC found in hyperthermophilic bacteria.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Thus, histone acetylation leads to gene activation, while histone deacetylation leads to a tighter histone-DNA interaction and, accordingly, to gene repression (Cecconi et al, 2003). Histone acetylation status is regulated by the opposing actions of histone acetyl-transferases (HATs) and histone deacetylases (HDACs) (Smith and Denu, 2009). During the last years HDAC-inhibitors have become one of the most promising classes of chemotherapeutics with profound antitumour effects (Glaser, 2007), and are successfully used to inhibit cell growth of lots of carcinoma cells in vitro (McBain et al, 1997;Shin et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…As modificações pós-traducionais (PTMs) mais comuns em histonas são acetilação, metilação (mono-, di-e tri-metilação), fosforilação e ubiquitinação, embora outros tipos de modificações como SUMOilação, ADP-ribosilação, citrulinação, biotinilação, adição de β-N-acetilglucosamina e isomerização de prolinas tenham sido também descritas (Kothapalli et al, 2005;Kouzarides, 2007;Smith & Denu, 2009;Sakabe et al, 2010;Banerjee & Chakravarti, 2011;Bannister & Kouzarides, 2011;Inbar-Feigenberg et al, 2013). Embora algumas PTMs possam ser adicionadas a histonas livres, a grande maioria dos padrões de PTMs de histonas é estabelecida durante e após a deposição das histonas no nucleossomo e depende das condições do microambiente onde essas histonas são incorporadas.…”
Section: H2axunclassified
“…Sendo assim, a acetilação geralmente leva a um afrouxamento da cromatina e predispõe a ativação da transcrição gênica através da exposição de sítios de ligação ao DNA (Figura 1, Tabela 2) (revisto por Smith & Denu, 2009;Khare et al, 2012;Miller & Grant, 2012). As histona-desacetilases (HDACs), presentes em diversos complexos protéicos, revertem a reação química desempenhada pelas HATs, removendo as marcas de acetilação das lisinas para restaurar suas cargas positivas e, portanto, estão geralmente associadas à repressão da transcrição gênica (revisto por Miller & Grant, 2012).…”
unclassified
See 1 more Smart Citation